2016
DOI: 10.47125/jesam/2016_sp2/02
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality and Nutrient Loading in the Coastal Waters of Boracay Island, Malay, Aklan, Central, Philippines

Abstract: This study analyzed the water quality dynamics in the coastal zone of Boracay Island in relation to anthropogenic activities and natural factors. Seven sites were studied where possible sources of nutrient inputs on spatial and temporal basis were identified. Water samples were evaluated using the Philippine Department of Environment and Natural Resources (DENR) regulatory standards. The coastal water quality was generally influenced by nutrient loading coming from untreated and partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Its coastline length, approximately 24.36 kilometers (PhilAtlas, n.d.), is noted for its four-kilometer stretch beaches and Long or White Beach (Smith et al, 2011). The island's landmass consists of a thin topsoil layer which covers coralline limestone known as karstic soil, which is a porous substance that allows domestic wastes and effluents to easily penetrate and contaminate both the groundwater and the coastal waters (Limates et al, 2016). Furthermore, Boracay Island can be divided into four zones, as shown in Figure 1, which were derived from the study of Tomoling (2014, unpublished), coinciding with the water quality monitoring stations set by DENR.…”
Section: Study Area and Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its coastline length, approximately 24.36 kilometers (PhilAtlas, n.d.), is noted for its four-kilometer stretch beaches and Long or White Beach (Smith et al, 2011). The island's landmass consists of a thin topsoil layer which covers coralline limestone known as karstic soil, which is a porous substance that allows domestic wastes and effluents to easily penetrate and contaminate both the groundwater and the coastal waters (Limates et al, 2016). Furthermore, Boracay Island can be divided into four zones, as shown in Figure 1, which were derived from the study of Tomoling (2014, unpublished), coinciding with the water quality monitoring stations set by DENR.…”
Section: Study Area and Zonesmentioning
confidence: 99%
“…However, the rapid growth of tourism back in the 1970s prompted haphazard practices on infrastructure and tourism management (Varga, n.d.). Additionally, the surge of tourists, unplanned developments, poor sewage system, and improper waste management caused a degenerating effect on the water quality and ecosystem of the island (Limates et al, 2016;Burgos, 2015). By 2018, a survey on the island's sewerage facilities showed that 85% of residential and commercial properties were pumping wastewater directly into the sea resulting in increased levels of coliform bacteria in its waters (DENR, 2019).…”
Section: Introductionmentioning
confidence: 99%